THE MODERATION EFFECT OF TRANSPARENCY ON THE INFLUENCE OF TAX AGGRESSIVENESS ON COMPANY VALUE (Case Study of Manufacturing Companies on the IDX from 2018 to 2022) - Novianti, Rini; Bakri, Asri Ady; Mayndarto, Eko Cahyo; Ningsih, Tri Widyastuti; Dewi, Mega Arisia (JURNAL ILMIAH EDUNOMIKA, 2024)
This research is motivated by the importance of company value as an illustration of public trust in the company. This research aims to determine the effect of tax aggressiveness on company value in manufacturing companies on the BEI from 2018 to 2022 and how transparency acts as a moderation on company value in manufacturing companies on the BEI from 2018 to 2022. This research method is descriptive quantitative. The population of this research is manufacturing companies on the IDX from 2018 to 2022 with a sampling technique, namely purposive sampling. The data used is secondary data. The data analysis technique used is Moderated Analysis Regression (MRA) using SPSS 26 software. The results of this research show that 1) Tax aggressiveness has a positive and significant effect on company value in manufacturing companies on the BEI from 2018 to 2022, and 2) Transparency is able to moderate the effect tax aggressiveness on company value in manufacturing companies on the IDX from 2018 to 2022. This suggests that if manufacturing companies want to increase company value, then the company should increase tax aggressiveness and transparency.